THE IMPACT OF BROILER FARMERS’ BEHAVIOR USING BROODING PERIOD EQUIPMENT ON PRODUCTIVITY AND INCOME IN SEMARANG REGENCY - Ahmad Wildan; Wulan Sumekar; Edjeng Suprijatna (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
It is crucial to pay great attention to the broodstock or brooding period and determine the maintenance success afterward. All important organs such as the immune system, respiratory tract, digestive tract, skeleton, and fur are experiencing development during the brooding period. This study aimed to: (1) analyze the impact of broiler farmers’ behavior in the brooding period on the productivity of broiler chickens in Semarang Regency, (2) evaluate the effect of the use of equipment in the brooding period on the productivity of broiler chickens in Semarang Regency, (3) evaluate the effect of broiler chickens productivity on the broiler farmers’ income in Semarang Regency. The research method used was survey research. This research was descriptive with a quantitative approach. Exogenous variables studied include the farmers’ behavior and brooding period equipment, while the endogenous variables are productivity and income. The population in this study was broiler farmers in Semarang Regency. Sampling using a purposive sampling technique. Determination of samples using random sampling. The unit of analysis of this research is broiler farmers in Semarang Regency. The number of respondents was 120 people. Path analysis was used to analyze the impact of farmers’ behavior in the brooding period on the productivity of broiler chickens and the income of broiler farmers, and the effect of broiler chicken productivity on broiler farmers. The results showed that farmers’ behavior (Knowledge, Attitude, Skills, and Motivation) and brooding equipment significantly affect the productivity of broiler chickens. Farmers’ knowledge in the brooding period significantly affects farmers’ income. Farmers’ skills during the brooding period significantly affect the income, and the productivity of broiler chickens significantly affects farmers’ income.